Miliary tuberculosis in an immunocompetent male with a fatal outcome. (2nd November 2016) - Dunphy, Louise; Keating, Elizabeth; Parke, T
Abstract : A man aged 33 years, born in Nepal, but resident in the UK for 7 years presented to the emergency department with a 4-day history of general malaise, fever (temperature 38.6°C) and a non-productive cough. His medical history was unremarkable and no high-risk behaviour was identified. Clinical examination confirmed decreased air entry bilaterally with bibasal crackles. He was tachycardic, with a heart rate of 120 bpm. Further investigation with a 12-lead ECG confirmed supraventricular tachycardia (SVT) which was terminated with vagal manoeuvres. His chest radiograph demonstrated left basal consolidation. His white cell count was 11×10 9 /L and his C reactive protein was 43.2 mg/L. His blood cultures revealed no growth. He was diagnosed with community-acquired pneumonia and started treatment with amoxicillin and clarithromycin. 3 days post admission, he was intubated for 24 hours in the Department of Intensive Care Medicine. Further episodes of SVT were observed and an ECHO showed a severely dilated and impaired left ventricle. Further chest radiographs illustrated diffuse consolidation with evidence of pulmonary oedema. HIV serology was negative. He developed transaminitis and thrombocytopenia. An ultrasound scan of his liver showed no obvious liver pathology. He remained tachypnoeic and due to worsening pulmonary oedema and extensive consolidation, he was readmitted to the intensive care unit. A CT abdomen with contrast showed an unusual pattern of lymphadenopathy with disproportionately enlarged coeliac axis nodes (5×7×5 cm) and minor para-aortic adenopathy, suspicious for lymphoma. On inserting his central venous catheter in his right internal jugular vein, pus was inadvertently aspirated from his right neck. Acid alcohol fast bacilli (AAFFB) were isolated from the pus and was subsequently identified as Mycobacterium tuberculosis . He started treatment with antitubercular medication rifater: a combination of rifampicin 720 mg od, isoniazid 300 mg po od and pyrazinamide 1750 mg. In addition, he received ethambutol 1000 mg po od and pyridoxine 5 mg. He developed worsening metabolic acidosis, pH 7.19, loss of respiratory compensation and pancytopenia. Right heart strain was evident on his Focused Intensive Care Echo. He developed an increased oxygen requirement and respiratory distress on the ventilator. An erect chest radiograph showed bilateral pneumothoraces and bronchopleural fistulae. A chest drain was inserted. Following discussion with the Cardiothoracic Surgeons, pleurodesis was not deemed possible. He developed inotropic-dependent shock with worsening lung compliance. As a result of his deteriorating ventilation, acidosis and hyperkalaemia, he started treatment with continuous veno-venous haemofiltration. With a diagnosis of miliary tuberculosis and SVT causing cardiogenic pulmonary oedema, this man sadly died with his family at his bedside 10 weeks following initial hospital presentation.